Analisis Kadar Protein pada Tulang Sapi dari Limbah Kaledo Asal Kota Palu Sulawesi Tengah - Cica Anisa; Baharuddin Hamzah (Media Eksakta, 2022)
Kaledo (donggala ox leg) is one of the famous culinary in Central Sulawesi. The number of restaurants that provide kaledo menus causes problems, due to the lack of utilization of the bone waste, causing problems in the environment. People still don't know that beef bones still contain protein. Protein serves as a form of new tissue during the growth and development of the body. This study aims to determine the protein content of beef bones from kaleo waste from the city of Palu, Central Sulawesi, which was taken randomly from a kaledo restaurant. Determination of protein content in beef bones from kale waste using the Kjeldhal method. In the results of calculations that have been carried out with three repetitions, it was found that the protein content in Repetition1 was 3.85%, Repetition2 was 3.59% and Repetition3 was 4.2%. The average protein content of beef bones from kale waste is 3.88%. The results of this study are expected to be a source of information about the protein content contained in beef bones from kaleo waste and can be used further as a substance in the utilization of bone waste.